STUDI KASUS KUALITAS PAKAN SELFMIXING BERDASARKAN UJI KADAR AIR DAN PROTEIN KASAR PADA PETERNAKAN LAYER DI KECAMATAN SRENGAT, KABUPATEN BLITAR - Lina Permanasari; Alfan Setya Winurdana; Risma Novela Esti (Universitas Islam Balitar, 2023)
This study was conducted to determine whether the feed used by layer breeders in Srengat sub-district was in accordance with Indonesian national standards or not. The sampling method used is using purposive random sampling method. The tests used in the study were testing the water content and crude protein content. The test was carried out in the animal feed laboratory of Blitar District. The data analysis used to draw conclusions was descriptive. The results showed that the feed used by layer breeders in Srengat sub-district, Blitar district was in accordance with Indonesian national standards, which was 60%.